Hydrogel and method for producing the same

JP2025040983APending Publication Date: 2025-03-26TOKYO WOMENS MEDICAL UNIV +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023147460
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-26

Smart Images

  • Figure 2025040983000030
    Figure 2025040983000030
  • Figure 2025040983000031
    Figure 2025040983000031
  • Figure 2025040983000032
    Figure 2025040983000032
Patent Text Reader

Abstract

To provide a hydrogel that exhibits a high breaking elongation and has both shape memory and self-repairing capabilities.SOLUTION: One embodiment of the present invention relates to a hydrogel comprising a polymer (A) having structural units derived from at least one monomer (A) selected from the group consisting of piperidine compounds having a (meth)acryloyl group and a predetermined substituent, and the like, as well as a method for producing the same.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hydrogel and a method for producing the same, etc. Specifically, the present invention relates to a hydrogel having a large breaking elongation, shape memory property and self-repair property, and a method for producing the same, etc. [Background technology]

[0002] Hydrogels, which are made of a three-dimensional polymer network structure, are essentially polymers with high affinity for water that swell in aqueous solvents. Hydrogels have biocompatibility, flexibility, transparency, and substance encapsulation properties based on their high water content, and are used in a wide range of fields from medicine to engineering. For example, biocompatible hydrogels can be used at the interface between living organisms and artificial objects, such as as a coating material for robots.

[0003] Meanwhile, temperature-responsive polymers are known as polymers whose solubility in a solvent changes in response to an external temperature stimulus. Temperature-responsive polymers include polymers having a lower critical solution temperature (LCST) and polymers having an upper critical solution temperature (UCST) due to a phase change caused by temperature. For example, Non-Patent Document 1 discloses a polymer having a UCST. In addition, Non-Patent Document 2 discloses a hydrogel containing poly(N-acryloylglycineamide). [Prior art documents] [Non-patent literature]

[0004] [Non-Patent Document 1] Y. Akiyama. Synthesis of Temperature-Responsive Polymers Containing Piperidine Carboxamide and N,N-diethylcarbamoly Piperidine Moiety via RAFT Polymerization. Macromol Rapid Commun. 2021, 42 (15) [Non-Patent Document 2] Z. Xu., et al., Poly(N-acryloyl glycinamide): a fascinating polymer that exhibits a range of properties from UCST to high-strength hydrogels, Chem Comm., 2018, 54, 10540. Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present embodiment is to provide a hydrogel that has a large breaking elongation, shape memory properties, and self-repair properties. [Means for solving the problem]

[0006] A preferred aspect of this embodiment is as follows.

[0007] 1. A hydrogel comprising a polymer (A) having structural units derived from one or more monomers (A) selected from the group consisting of compounds represented by the following formula (1) and compounds represented by the following formula (2):

[0008] [ka] (In formula (1), R 11 is hydrogen or a methyl group, R 12 ~R 16 each independently represents hydrogen, -C(=O)NH2, or -C(=O)-NH-CH2-C(=O)-NH2, and R 12 ~R 16 At least one of the groups is -C(=O)NH2 or -C(=O)-NH-CH2-C(=O)-NH2.

[0009] [ka] (In formula (2), R 21 is hydrogen or a methyl group, R 22 is -C2H5 or -C3H7.)

[0010] 2. The hydrogel described in 1 above, wherein the polymer (A) is a homopolymer.

[0011] 3. The hydrogel according to 1 or 2 above, wherein the polymer (A) is a copolymer.

[0012] 4. The hydrogel according to 3 above, wherein the polymer (A) is a copolymer further comprising a constituent unit derived from a monomer (B) that is copolymerizable with the monomer (A).

[0013] 5. The hydrogel according to any one of the above 1 to 4, wherein the monomer (A) contains a compound represented by the formula (1).

[0014] 6. The hydrogel according to any one of 1 to 5 above, wherein the monomer (A) comprises one or more compounds selected from the group consisting of compounds represented by the following formulas (11) to (15):

[0015] [ka]

[0016] 7. The hydrogel according to any one of 1 to 6 above, wherein the monomer (A) comprises N-(meth)acryloyl nipecotamide and / or N-(meth)acryloyl-2-aminobutyramide.

[0017] 8. The hydrogel according to 3 above, wherein the polymer (A) has a structure represented by the following formula (31) and / or the following formula (32):

[0018] [ka] (In formula (31), m and n each independently represent an integer of 1 or more.)

[0019] [ka] (In formula (32), m and n each independently represent an integer of 1 or more.)

[0020] 9. The hydrogel described in any one of 1 to 8 above, wherein the monomer (A) contains N-acryloylnipecotamide.

[0021] 10. The hydrogel according to any one of 1 to 9 above, which is transparent.

[0022] 11. The hydrogel according to any one of 1 to 10 above, further comprising an additive that does not constitute the polymer (A).

[0023] 12. The hydrogel according to claim 11, wherein the additive is alginic acid and / or gelatin.

[0024] 13. The hydrogel according to any one of 1 to 12 above, wherein the weight ratio of the polymer (A) in the hydrogel is 5 to 60% by weight.

[0025] 14. The hydrogel according to any one of 1 to 12 above, wherein the weight ratio of the polymer (A) in the hydrogel is 20 to 50% by weight.

[0026] 15. The hydrogel according to any one of 1 to 14 above, wherein the weight proportion of the polymer (A) when immersed in water for 24 hours is 20 to 40% by weight.

[0027] 16. The hydrogel according to any one of 1 to 15 above, wherein the number average molecular weight of the polymer (A) is 6,500 Da to 1,000,000 Da.

[0028] 17. The hydrogel described in 16 above, wherein the number average molecular weight of the polymer (A) is 31,000 Da or more.

[0029] 18. The hydrogel described in any one of 1 to 17 above, having an elongation at break of 1500% or more in a tensile test in accordance with JIS K6251:2017, dumbbell No. 7.

[0030] 19. A step of preparing a reaction liquid containing an aqueous solvent, a polymerization initiator, and a monomer component containing one or more monomers (A) selected from the group consisting of a compound represented by the following formula (1) and a compound represented by the following formula (2); A step of polymerizing a monomer component in the reaction liquid; A method for producing a hydrogel comprising the steps of:

[0031] [ka] (In formula (1), R 11 is hydrogen or a methyl group, R 12 ~R 16 each independently represents hydrogen, -C(=O)NH2, or -C(=O)-NH-CH2-C(=O)-NH2, and R 12 ~R 16 At least one of the groups is -C(=O)NH2 or -C(=O)-NH-CH2-C(=O)-NH2.

[0032] [ka] (In formula (2), R 21 is hydrogen or a methyl group, R 22 is -C2H5 or -C3H7.)

[0033] 20. The method for producing a hydrogel according to the above 19, wherein the concentration of the monomer (A) in the reaction liquid is 20 to 60% by weight.

[0034] 21. The method for producing a hydrogel described in 19 or 20 above, wherein the polymerization initiator is a photoradical polymerization initiator.

[0035] 22. A cell culture substrate or cell culture scaffold comprising the hydrogel according to any one of 1 to 18 above. Effect of the Invention

[0036] According to the present embodiment, a hydrogel having a large breaking elongation, shape memory properties, and self-repairing properties can be provided. [Brief description of the drawings]

[0037] [Figure 1] 1 is a graph showing the results of a tensile strength test of the hydrogel of Example 1. [Figure 2A] 1 is a graph showing the results of dynamic viscoelasticity measurement (strain dependency) of the hydrogel of Example 2. [Figure 2B] 1 is a graph showing the results of dynamic viscoelasticity measurement (angular frequency dependence) of the hydrogel of Example 2. [Figure 3A] 1 is a photograph of a gel after the first tensile strength test in Example 3 and after immersion in water for 30 minutes. [Figure 3B] 1 is a graph showing the results of a repeated tensile strength test in Example 3. [Figure 4A] 13 is a photograph showing the results of rebinding of cut hydrogel in Example 4. [Figure 4B] FIG. 13 is a schematic diagram showing the state of molecules when the cut gel in Example 4 is recombined by increasing the temperature and then decreasing the temperature. [Diagram 5] 13 is a photograph showing that in Example 5, the cut gel was reassembled by freezing and then thawing the gel. [Figure 6A] 1 is a graph showing the relationship between the monomer weight concentration during gel preparation and the weight change rate of the obtained gel due to immersion in water in Example 6. [Figure 6B] 1 is a graph showing the relationship between the monomer concentration during gel preparation, and the gel content 1 before immersion in water and the gel content 2 after immersion in water in Example 6. [Figure 7]FIG. 1 is a diagram showing a schematic structure of a hydrogel containing gelatin. [Figure 8A] 1 is a photograph of a hydrogel containing gelatin of Example 8-1. [Figure 8B] 1 is a graph showing the results of a tensile strength test of a hydrogel containing gelatin of Example 8-1. [Figure 8C] 1 is a photograph showing the results of immersing the alginic acid-containing hydrogel of Example 8-2 in an aqueous solution containing Ca2+ or in water not containing Ca2+. [Figure 8D] 1 is a graph showing the results of a tensile strength test of the alginic acid-containing hydrogel of Example 8-2. [Figure 8E] 1 is a photograph showing the results of rebinding of the hydrogel that was cut in Example 8-2. [Figure 9A] FIG. 13 is a graph showing the absorbance of the external solution when a hydrogel containing Rose Bengal is immersed in water in Example 9. [Figure 9B] FIG. 13 is a graph showing the amount of Rose Bengal in the external solution released from the hydrogel in Example 9. [Figure 10] 1 is a graph showing the measurement results of the light transmittance of the hydrogel in Example 10. [Figure 11A] 1 is a photograph showing the results of a bottle tightening test of the gel obtained in Example 11-1. [Figure 11B] 1 is a photograph of the gel obtained in Example 11-2. [Figure 11C] 1 is a graph showing the results of a tensile strength test of the hydrogel of Example 11-2. [Figure 12] 1 shows a 1H-13C HSQC NMR chart of N-acryloyl-2-piperidinecarboxamide synthesized in Synthesis Example 1. [Figure 13] 1 shows a 1H-13C HSQC NMR chart of N-acryloyl-4-piperidinecarbonitrile synthesized in Synthesis Example 2. [Figure 14] 1 shows an NMR chart of N-acryloyl-3,5-piperidinedicarboxamide synthesized in Synthesis Example 3. [Figure 15]1 shows an NMR chart of acryloyl-N-(2-amino-2-oxoethyl)piperidine-3-carboxamide synthesized in Synthesis Example 4. [Figure 16] 1H NMR chart of N-acryloyl-2-aminobutyramide synthesized in Example 11. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0038] <Hydrogel> The hydrogel (also simply referred to as "gel") of this embodiment preferably contains a polymer (A) having constitutional units derived from one or more monomers (A) selected from the group consisting of compounds represented by the following formula (1) and compounds represented by the following formula (2).

[0039] [ka] (In formula (1), R 11 is hydrogen or a methyl group, R 12 ~R 16 each independently represents hydrogen, -C(=O)NH2, or -C(=O)-NH-CH2-C(=O)-NH2, and R 12 ~R 16 At least one of the groups is -C(=O)NH2 or -C(=O)-NH-CH2-C(=O)-NH2.

[0040] [ka] (In formula (2), R 21 is hydrogen or a methyl group, R 22 is -C2H5 or -C3H7.)

[0041] In this specification, a "structural unit derived from a monomer" is also referred to as a "monomer unit". The terms "structural unit derived from a monomer" and "monomer unit" refer to a structural unit in a homopolymer or copolymer derived from a monomer, and the word "monomer" is sometimes used to mean "monomer unit". In addition, a compound represented by formula (1) and a compound represented by formula (2) are also referred to as a "compound of formula (1)" and a "compound of formula (2)", respectively.

[0042] (Monomer (A)) Monomer (A) is at least one selected from the group consisting of compounds represented by the above formula (1) and compounds represented by the above formula (2), and may be a mixture of two or more. Monomer (A) may be one or more selected from the compounds of formula (1), may be one or more selected from the compounds of formula (2), or may contain both the compounds of formula (1) and the compounds of formula (2).

[0043] As described above, the compounds represented by formula (1) and formula (2) are polymerizable monomers having a (meth)acryloyl group as a polymerizable functional group. In this specification, the (meth)acryloyl group means either an acryloyl group or a methacryloyl group, and the "(meth)" in (meth)acrylate and the like has the same meaning. Each compound will be described below.

[0044] As described above, the compound represented by formula (1) is a substituted piperidine compound in which, in addition to the N-(meth)acryloyl group, at least one of the hydrogen atoms bonded to the piperidine ring is replaced with -C(=O)NH2 (carboxamide group) and / or -C(=O)-NH-CH2-C(=O)-NH2 (2-amino-oxoethyl-carboxamide group).

[0045] In formula (1), R 11 is hydrogen or a methyl group, and in one embodiment is preferably hydrogen.

[0046] In formula (1), R 12 ~R 16 each independently represents hydrogen, -C(=O)NH2, or -C(=O)-NH-CH2-C(=O)-NH2, and R 12 ~R 16 At least one of the groups is -C(=O)NH2 or -C(=O)-NH-CH2-C(=O)-NH2. When one monomer has multiple substituents, it may have multiple of either -C(=O)NH2 or -C(=O)-NH-CH2-C(=O)-NH2, or it may have both.

[0047] In one embodiment, R 12 ~R 16 Among these, it is preferred that 1 to 3 are -C(=O)NH2 or -C(=O)-NH-CH2-C(=O)-NH2, it is more preferred that 1 to 3 are -C(=O)NH2, it is even more preferred that 1 to 2 are -C(=O)NH2, and it is even more preferred that 1 is -C(=O)NH2. 12 ~R 16 Of these, it is preferred that one is -C(=O)NH2, and R 12 ~R 16 Of these, R 13 It is more preferable that R is -C(=O)NH2 and the others are hydrogen. 12 ~R 16 If two of the are substituted, for example, R 13 and R 15 are each independently -C(=O)NH2 and / or -C(=O)-NH-CH2-C(=O)-NH2, and R 12 , R 14 , and R 16 is preferably hydrogen.

[0048] Examples of the compound of formula (1) include, but are not limited to, compounds represented by the following formulae (11) to (15).

[0049] [ka] [ka]

[0050] The names of the compounds of formulas (11) to (15) are as follows. Formula (11): Acryloyl-(piperidine-3,5-dicarboxamide) Formula (12): N-Acryloyl-N'-(2-amino-2-oxoethyl)nipecotamide Formula (13): N-Acryloyl-isonipecotamide (N-Acryloyl-piperidine-4-carboxamide) Formula (14): N-Acryloyl-nipecotamide (N-Acryloyl-piperidine-3-carboxamide) Formula (15): N-Acryloyl-piperidine-2-carboxamide

[0051] The solubility of monomers in water varies depending on their structure, and when compounds with low solubility are used, the gel tends to be hard, whereas when compounds with high solubility are used, the gel tends to be soft. Therefore, it is possible to control the viscoelasticity of the gel by combining different types of monomers.

[0052] In the compound of formula (2), R 21 R is hydrogen or a methyl group, and in one embodiment is preferably hydrogen. 22 is -C2H5 or -C3H7. In one embodiment, R 22 is preferably -C2H5. In one embodiment, the compound of formula (2) is 22 is preferably N-acryloyl-2-aminobutyramide, in which N is -C2H5. N-acryloyl-2-aminobutyramide is a novel compound and can be synthesized by the method described in Example 11 below.

[0053] The polymer (A) may be a homopolymer or a copolymer. When the polymer (A) is a copolymer, the polymer may contain two or more monomer units selected from the monomer (A). Alternatively, the polymer may contain, in addition to one or more monomer units selected from the monomer (A), a monomer unit derived from a monomer (B) having a structure different from that of the monomer (A). The monomer (B) will be described later. The copolymer may be a random copolymer or a block copolymer, but is usually preferably a random copolymer. In one embodiment, two or more monomers are copolymerized in a multi-component manner to form a block copolymer, which allows the physical properties of the gel to be controlled.

[0054] In one embodiment, the monomer (A) is preferably 60 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, and even more preferably 90 mol% or more, relative to 100 mol% of the monomers forming the polymer (A).

[0055] In one embodiment, it is preferable that the monomer (A) contains N-acryloylnipecotamide represented by the above formula (14). For example, the content of monomer units derived from N-acryloylnipecotamide in the total amount (100 mol%) of monomer units constituting the polymer (A) is preferably 50 mol% or more, more preferably 70 mol% or more, and even more preferably 90 mol% or more, and may be 100 mol% (homopolymer).

[0056] When the monomer (A) contains N-acryloylnipecotamide, the polymer (A) has a structure represented by the following formula (16): In one embodiment, the polymer (A) is preferably poly(N-acryloylnipecotamide).

[0057] [ka] (In formula (16), n represents an integer of 1 or more, preferably 2 or more. Although n is not limited, it is preferable that n is, for example, 20≦n≦2000.)

[0058] When the monomer (A) contains N-acryloyl-2-aminobutyramide, the polymer (A) has a structure represented by the following formula (21): In one embodiment, the polymer (A) is preferably poly(N-acryloyl-2-aminobutyramide).

[0059] [ka] (In formula (21), m represents an integer of 1 or more, preferably 2 or more. m is not limited, but is preferably, for example, 20≦m≦2000.)

[0060] In one embodiment, the polymer (A) may be a copolymer of N-acryloylnipecotamide and N-acryloyl-2-aminobutyramide. In the case of this copolymer, the ratio (mol) of N-acryloyl-2-aminobutyramide to the total of N-acryloylnipecotamide and N-acryloyl-2-aminobutyramide is not limited, but is preferably 0.1 mol% or more, more preferably 1 mol% or more, and is preferably 50 mol% or less, more preferably 10 mol% or less.

[0061] (Monomer (B)) In one embodiment, the polymer (A) constituting the hydrogel may be a copolymer having, in addition to a constituent unit derived from the monomer (A), a constituent unit derived from a monomer (B) copolymerizable with the monomer (A). The monomer (B) is different from the monomer (A).

[0062] Monomer (B) is not limited, but may be, for example, a compound in which at least one hydrogen bonded to the piperidine ring of N-(meth)acryloylpiperidine is substituted and does not fall under formula (1). For example, a compound in which at least one hydrogen bonded to the piperidine ring of N-(meth)acryloylpiperidine is substituted with -CN. In addition, monomer (B) may be, for example, alkyl-(meth)acrylamides such as N-butyl-(meth)acrylamide, alkyl-(meth)acrylates such as butyl-(meth)acrylate, etc.

[0063] Copolymers having structural units derived from monomer (A) and monomer (B) include, but are not limited to, copolymers having a structure of the following formula (31) or formula (32). The copolymers having the structure of formula (31) and / or formula (32) may be random copolymers or block copolymers, but are preferably random copolymers.

[0064] [ka] (In formula (31), m and n each independently represent an integer of 1 or more (preferably an integer of 2 or more). m and n are not limited, but are preferably, for example, 1≦m≦2000, 1≦n≦2000. m:n is not limited, but is preferably 100:1 to 1:100, and is, for example, preferably about 3:2.)

[0065] [ka] (In formula (32), m and n each independently represent an integer of 1 or more (preferably an integer of 2 or more). m and n are not limited, but for example, preferably 1≦m≦2000, 1≦n≦2000. m:n is not limited, but is preferably 100:1 to 1:100, and for example, is preferably about 3:2.)

[0066] In one embodiment, the components constituting the polymer (A) may include a crosslinking agent as the monomer (B). In one aspect, the crosslinking agent is preferably a substance that is biocompatible and capable of crosslinking monomers. For example, the crosslinking agent may preferably be a compound having at least two acrylamide or methacrylamide groups in the molecule. Specific examples of the crosslinking agent include N,N'-methylenebisacrylamide (MBAAm), ethylene glycol dimethacrylate (EGDMA), and N,N'-methylenebismethacrylamide (MBMAAm).

[0067] The number average molecular weight of the polymer (A) in the hydrogel of this embodiment is not limited, but is preferably 6500 Da or more, more preferably 7000 Da or more, even more preferably 10,000 Da or more, and may be 31,000 Da or more, and is preferably 1,000,000 Da or less, more preferably 700,000 Da or less, and even more preferably 500,000 Da or less. The degree of polymerization of the polymer (A) is not limited, but is, for example, preferably 20 or more, more preferably 40 or more, and the upper limit is preferably 5,000 or less, more preferably 2,000 or less. The number average molecular weight can be calculated by the method described in the Examples.

[0068] The concentration of the polymer (A) in the hydrogel is not limited, but is preferably 5% by weight or more, more preferably 10% by weight or more, even more preferably 20% by weight or more, and may be 30% by weight or more, 35% by weight or more, and is preferably 60% by weight or less, more preferably 55% by weight or less, and even more preferably 50% by weight or less. The concentration of the polymer (A) is determined by measuring the weight before and after freeze-drying the gel, Weight after freeze-drying / weight before freeze-drying x 100 (%) In one embodiment, the weight percentage of the polymer (A) when the hydrogel is immersed in water for 24 hours is not limited, but is preferably, for example, 20 to 40% by weight.

[0069] In one embodiment, the hydrogel has, in dynamic viscoelasticity measurement (temperature: 25°C), a G' (storage modulus) of preferably 1000 Pa to 1,000,000 Pa and a G'' (loss modulus) of preferably 10 Pa to 10,000 Pa, although this is not limited thereto.

[0070] The hydrogel of this embodiment may contain additives that do not constitute the polymer (A) as long as the effects of the present invention are not impaired. The additives are not particularly limited, but examples thereof include gelatin, alginic acid, dyes, medicines, preservatives, bactericides, rust inhibitors, antioxidants, stabilizers, fragrances, surfactants, various metal ions, etc. The type and concentration of the additives can be appropriately selected depending on the application.

[0071] In one embodiment, the hydrogel may contain gelatin. By including gelatin, a hydrogel with a higher breaking elongation can be obtained. FIG. 7 shows a schematic diagram of the molecular state when gelatin is mixed with a monomer component and a polymerization initiator, and the monomer component is polymerized. By including gelatin, an interpenetrating polymer network (IPN structure) is formed, and the intermolecular force and the degree of molecular crowding due to hydrogen bonds between polymers increase, which is presumed to change the mechanical properties of the gel and form a gel with a higher breaking elongation. The concentration of gelatin in the hydrogel is not limited, but is, for example, preferably 0.01% by weight or more, more preferably 0.1% by weight or more, and also preferably 10.0% by weight or less, more preferably 1.0% by weight or less.

[0072] In one embodiment, the hydrogel may contain alginic acid. By containing alginic acid, a gel with a larger breaking elongation can be obtained. The alginic acid may be an alginate such as sodium alginate. When alginic acid is contained, an IPN structure is formed in the gel as in the case of containing gelatin. The concentration of alginic acid in the hydrogel is not limited, but is preferably 0.01% by weight or more, more preferably 0.1% by weight or more, and is preferably 10.0% by weight or less, more preferably 5.0% by weight or less, and even more preferably 1.0% by weight or less.

[0073] It is also known that alginic acid forms a cross-linked structure with calcium ions. When the hydrogel containing the alginic acid of this embodiment is immersed in a solution containing calcium ions, a polymer network structure formed by alginic acid and calcium and a polymer structure by polymer (A) are formed. This makes the hydrogel hard and less likely to swell even when immersed in water, and the breaking elongation of the hydrogel is even higher than when it does not contain calcium. Ca in a solution containing calcium ions 2+ The concentration of is not limited, but is, for example, preferably 0.01 M or more, more preferably 0.1 M or more, and is preferably 10 M or less, more preferably 2 M or less.

[0074] In one embodiment, the hydrogel may contain, as an additive, a water-soluble polymer other than those mentioned above. Examples of the water-soluble polymer include polyvinylpyrrolidone, a vinylpyrrolidone copolymer such as a copolymer of vinyl alcohol and vinylpyrrolidone, a copolymer of ether-modified vinyl alcohol and vinylpyrrolidone, and a copolymer of vinylpyrrolidone and vinyl acetate, etc., polyvinyl alcohol, polyacrylic acid, sodium polyacrylate, sodium carboxymethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, dextran, polyethylene glycol, polyoxazoline, various proteins, and nucleic acids.

[0075] The hydrogel of the present embodiment has a large breaking elongation, shape memory and self-repairing properties. In one aspect, the hydrogel is transparent. The hydrogel will be specifically described below.

[0076] In one embodiment, the hydrogel is transparent in a temperature range of 5 to 60°C. In one aspect of the present invention, the hydrogel has a light transmittance of preferably 65% ​​or more, more preferably 70% or more in the visible region of 400 nm to 800 nm. In one aspect, the hydrogel has a light transmittance of preferably 65% ​​or more, more preferably 70% or more at a wavelength of 400 nm, and a light transmittance of preferably 70% or more, more preferably 75% or more in the entire region of 450 to 800 nm. In this specification, the optical path length of the sample (gel thickness) in measuring the light transmittance of the gel is 1 cm. In one aspect, the hydrogel is preferably colorless and transparent. Since the hydrogel is transparent (high light transmittance), it can be used for members requiring visibility on the opposite side of the gel. In one aspect, the hydrogel can be colored by suppressing light transmission of only a certain wavelength range by an additive.

[0077] Generally, when the number average molecular weight of a polymer is large, it becomes hydrophobic and forms a phase separation structure with water, becoming cloudy. However, the inventors of the present invention have found that the polymer contained in the gel of this embodiment can form a transparent gel even if the number average molecular weight is large. For example, poly(N-acryloylnipecotamide) is usually known to be hydrophobic when the number average molecular weight is about 30,000 Da or more, but the inventors have found that a hydrogel containing this polymer becomes a transparent gel even if the number average molecular weight is large.

[0078] The hydrogel of this embodiment has a large breaking elongation and is highly stretchable. Specifically, the breaking elongation (extension ratio) in a tensile test of the gel in accordance with JIS K6251:2017, dumbbell-shaped No. 7 (measurement temperature: 20 to 25°C, humidity: 50 to 65%) is preferably 700% or more, more preferably 800% or more, even more preferably 1200% or more, even more preferably 1500% or more, even more preferably 1700% or more, and the upper limit is not limited, but is, for example, 6000% or less. In addition, as described above, when an IPN structure is formed in the gel by adding an additive such as gelatin or alginic acid, a hydrogel with a larger breaking elongation can be obtained, and a breaking elongation of 2000% or more, or 3000% or more can be achieved in some cases. Due to the large breaking elongation and good stretchability, the hydrogel of this embodiment is suitable for use in, for example, a robot covering material, a cell / tissue culture bed, etc. In one aspect, the hydrogel of the present embodiment exhibits high extensibility compared to the hydrogel containing poly(N-acryloylglycine amide) described in Non-Patent Document 2, even though the gel has a low polymer concentration.

[0079] The hydrogel of the present embodiment has a shape memory property that returns to its original shape after being deformed by tension or the like. For example, when the hydrogel is stretched by applying stress, the gel is stretched, but when it is subsequently immersed in water without applying stress, it returns to its original shape, and its mechanical properties also recover to a state close to that before it was stretched (see Examples). When the gel of the present embodiment is stretched, water is released and the weight of the gel decreases, but when the stretched gel is immersed in water, water is absorbed and the weight of the gel increases, and the gel recovers to a weight close to the original weight. The conditions for immersing in water to recover the shape are not limited, and can be set depending on the structure of the polymer constituting the gel, its concentration, temperature, degree of deformation, and the like. In one aspect, for example, the deformed gel can be restored to its original shape by immersing the gel in water at 10°C to 40°C for 10 minutes to 60 minutes. Thus, the hydrogel of the present embodiment has a shape memory property, and is therefore less likely to retain a history due to stretching, and can be stretched and used repeatedly.

[0080] Generally, hydrogels are mostly composed of water, and therefore it is difficult to make them remember the shape before deformation due to their structural flexibility. On the other hand, the hydrogel of the present embodiment has the property of remembering the shape given to it at first and recovering to the original shape by immersion in water after deformation, as described above, and is therefore suitable for use as a highly functional soft material, artificial muscle, stimuli-responsive sensor, and the like.

[0081] Furthermore, the hydrogel of this embodiment has a self-repairing property that, even if broken, it recombines and returns to its original state by a temperature stimulus or the like. For example, when a plurality of gel fragments broken by cutting or the like are heated with at least a portion of the fragments in contact (or close to each other), and then cooled, the gels can be recombined. This is presumed to be because the hydrogen bonds of the polymers in the gel are released by heating, and molecular motion is promoted, so that the contact interfaces between the gels are mixed, and then the temperature is lowered, so that the molecules in the gel including the contact interfaces are recombined by hydrogen bonds. FIG. 4B is a schematic diagram showing the state of the molecules when the cut gel is recombined. The conditions for self-repairing the gel are not limited, and can be appropriately set depending on the composition of the gel, etc. In one embodiment, for example, the cut gel fragments are heated in a state of contact or close to each other, and are treated at preferably 60°C to 100°C for 30 minutes to 2 hours. The heating temperature may be 60°C to 80°C. Subsequently, the gel fragments can be recombined by lowering the temperature of the heated gel and leaving it at a temperature of preferably 10° C. or higher but 30° C. or lower (preferably room temperature of about 20 to 25° C.) for about 5 minutes to 1 hour. In one aspect, the gel of this embodiment can self-repair even under conditions of a lower heating temperature than the hydrogel containing poly(N-acryloylglycineamide) described in Non-Patent Document 2.

[0082] As another method for self-repairing the gel, the hydrogel of the present embodiment can be used to freeze a plurality of gel fragments broken by cutting or the like in a state where at least a portion of the fragments are in contact (or in close proximity) with each other, and then melted to recombine the gels. In one aspect, for example, the gel is frozen by leaving a plurality of cut gel fragments in contact or in close proximity, preferably at -50°C to -20°C, for preferably 30 minutes or more (more preferably 30 minutes or more and 2 hours or less). The frozen gel is then left to stand for about 30 minutes to 2 hours, preferably at 10°C to 25°C (more preferably at room temperature of about 20 to 25°C), to melt the gel fragments, thereby recombine the gel fragments. As described above, the hydrogel of the present embodiment can self-repair by heating or by freezing and thawing, and therefore can be used in a wide range of applications as a self-repairing material, and a variety of materials can be used in combination with the hydrogel.

[0083] As another method for rebinding a gel, when the hydrogel contains alginic acid, multiple gel fragments broken by cutting or the like can be rebound by immersing the gel in a solution containing calcium ions with at least a portion of the fragments in contact (or in close proximity) with each other. This is presumably due to the formation of a cross-linked structure between the alginic acid and calcium.

[0084] In the gel of this embodiment, instead of the above-mentioned cut gel, gels that have been separately produced can be bonded together by applying a temperature stimulus or the like.

[0085] <Hydrogel manufacturing method> The method for producing the hydrogel of this embodiment includes the steps of: A step of preparing a reaction liquid containing an aqueous solvent, a polymerization initiator, and a monomer component containing one or more monomers (A) selected from the group consisting of a compound represented by formula (1) and a compound represented by formula (2) (also referred to as a "reaction liquid preparation step"); A step of polymerizing the monomer components in the reaction liquid (also referred to as a "polymerization step"); Each step will be described below.

[0086] (Reaction solution preparation process) In the reaction liquid preparation step, a reaction liquid is prepared that contains an aqueous solvent, a polymerization initiator, and a monomer component that contains one or more monomers (A) selected from the group consisting of compounds represented by formula (1) and compounds represented by formula (2).

[0087] (Monomer component) The monomer component includes one or more monomers (A) selected from the group consisting of compounds represented by formula (1) and compounds represented by formula (2). The above description of the hydrogel applies to the compounds represented by formula (1) and formula (2). The monomer (A) may be one or more. The monomer component may also include other monomers other than the monomer (A). The other monomers include monomers (B) that are different from the monomer (A) and are copolymerizable with the monomer (A). The above description of the monomer (B) in the description of the hydrogel applies to the monomer (B). Of the total amount of the monomer components, the content of the monomer (A) is, for example, preferably 50 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, and may be 100 mol%.

[0088] In one embodiment, for example, the content of N-acryloylnipecotamide in the total amount of monomer (A) is preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 90 mol% or more, and may be 100 mol%.

[0089] The concentration of the monomer component in the reaction solution is not limited, but is preferably 5% by weight or more, more preferably 10% by weight or more, and even more preferably 20% by weight or more, and may be 30% by weight or more, 35% by weight or more, and may be preferably 60% by weight or less, or 50% by weight or less. The hydrogel of this embodiment can produce a transparent gel with high breaking elongation even if the concentration of the monomer component is high. In one embodiment, the concentration of the monomer component in the reaction solution is preferably 20 to 50% by weight. In one embodiment, when the monomer (A) contains N-acryloylnipecotamide as a main component, a hydrogel with a small volume change (swelling or shrinkage) when immersed in water can be obtained when the concentration of the monomer component in the reaction solution is about 35 to 45% by weight.

[0090] (Water-based solvent) The aqueous solvent may be water or a mixed solvent of water and an organic solvent compatible with water, preferably water. The solvent is preferably a solvent capable of dissolving the monomer components. Examples of the organic solvent compatible with water include N,N-dimethylformamide (DMF), tetrahydrofuran (THF), and dimethylsulfoxide (DMSO). These organic solvents may be used alone or in combination of two or more. When a mixed solvent is used, the blending ratio (volume ratio) of water to the organic solvent is preferably 9:1 to 4:6.

[0091] (Polymerization initiator) The polymerization initiator (also simply referred to as "initiator") is not limited, and a radical polymerization initiator is preferable. Examples of the radical polymerization initiator include a photoradical polymerization initiator and a thermal radical polymerization initiator, and in one embodiment, a photoradical polymerization initiator is preferable. A known compound can be used as the polymerization initiator.

[0092] The photoradical polymerization initiator is not limited as long as it is cleaved by irradiation with active light such as ultraviolet light to generate radicals. The photoradical polymerization initiator is preferably one having sensitivity to ultraviolet light having a wavelength shorter than 405 nm, and from the viewpoint of being able to fully utilize the energy emitted from the light source and being excellent in productivity, it is preferable that the maximum absorption wavelength is 300 nm to 400 nm, and more preferably 300 nm to 380 nm. The photoradical polymerization initiator is not particularly limited, and examples thereof include alkylphenone radical polymerization initiators, acylphosphine oxide radical polymerization initiators, and oxime ester radical polymerization initiators. These photopolymerization initiators may be used alone or in combination of two or more.

[0093] Examples of the photopolymerization initiator include α-hydroxyalkylphenone-based radical photopolymerization initiators such as 2-hydroxy-2-methyl-1-phenylpropan-1-one (trade name: OMNIRAD (Irgacure) 1173, manufactured by BASF Japan Ltd.), 1-hydroxycyclohexyl phenyl ketone (trade name: OMNIRAD (Irgacure) 184, manufactured by BASF Japan Ltd.), 4'-(2-hydroxyethoxy)-2-hydroxy-2-methylpropiophenone (trade name: OMNIRAD (Irgacure) 2959, manufactured by BASF Japan Ltd.), and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylpropan-1-one (trade name: OMNIRAD 127, manufactured by BASF Japan Ltd.).

[0094] Examples of the acylphosphine oxide photopolymerization initiator include benzoyl-diphenylphosphine oxide, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2,3,5,6-tetramethylbenzoyl-diphenylphosphine oxide, 3,4-dimethylbenzoyl-diphenylphosphine oxide, 2,4,6-trimethylbenzoyl-phenylethoxyphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, bis(2,6-dimethylbenzoyl)-ethylphosphine oxide, etc. Commercially available products of the acylphosphine oxide photoradical polymerization initiator include OMNIRADTPO, OMNIRADTPO-L, OMNIRAD819, etc.

[0095] It is also preferable to use lithium phenyl(2,4,6-trimethylbenzoyl)phosphinate (manufactured by Tokyo Chemical Industry Co., Ltd.) as the photopolymerization initiator.

[0096] The thermal radical polymerization initiator is not particularly limited as long as it is cleaved by heat to generate radicals, and examples thereof include organic peroxides such as benzoyl peroxide; azo-based polymerization initiators such as azobiscyanovaleric acid, azobisisobutyronitrile (AIBN), azobisamidinopropane dihydrochloride, and 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride; and persulfates such as potassium persulfate and ammonium persulfate. These thermal polymerization initiators may be used alone or in combination of two or more. In addition, a redox polymerization initiation system in which ammonium persulfate and tetramethylethylenediamine are combined may be used.

[0097] The amount of the polymerization initiator (preferably a photoradical polymerization initiator) is not limited, but is preferably 0.001 parts by weight or more, more preferably 0.01 parts by weight or more, and also preferably 1 part by weight or less, more preferably 0.5 parts by weight or less, relative to 100 parts by weight of the total amount of the monomers used in the production of the hydrogel. The concentration of the polymerization initiator (preferably a photoradical polymerization initiator) in the solution when polymerizing the monomer is not limited, but is, for example, preferably 0.001% by weight or more, more preferably 0.005% by weight or more, and may be 0.2% by weight or more, and may be preferably 8% by weight or less, more preferably 6% by weight or less, and even more preferably 5% by weight or less, and may be 3% by weight or less. If the concentration of the radical polymerization initiator is too high, the amount of polymerization initiator remaining in the gel may increase, or the polymer may not easily become high molecular weight. If the concentration of the radical polymerization initiator is too high, the gel may become non-uniform. On the other hand, if the concentration of the radical polymerization initiator is too low, the monomers may not react sufficiently during the polymerization reaction.

[0098] The molecular weight of the polymer synthesized can be adjusted by adjusting the concentration of the polymerization initiator. Increasing the concentration of the polymerization initiator tends to decrease the molecular weight of the polymer, whereas decreasing the concentration of the polymerization initiator tends to increase the molecular weight of the polymer.

[0099] When the hydrogel contains an additive that does not constitute a polymer, the additive may be added to the reaction solution or after the gel is prepared. In one embodiment, when a compound that forms an IPN structure, such as alginic acid or gelatin, is used as an additive, it is preferable to add the additive to the reaction solution before the polymerization reaction.

[0100] In preparing the reaction solution, the order of mixing each component is not limited, and the monomer component and the polymerization initiator may be simultaneously dissolved and mixed in an aqueous solvent, or the monomer component and the polymerization initiator may be separately dissolved in an aqueous solvent and the solutions may be mixed. In one embodiment, a solution in which components other than the polymerization initiator are mixed may be prepared, and the polymerization initiator may be added immediately before the polymerization reaction. As a means for mixing the components, a known device such as an ultrasonic dispersion device may be used. The temperature during mixing is not particularly limited, and may be, for example, room temperature (preferably 5 to 40°C, more preferably 10 to 35°C). In addition, the mixed solution may be degassed before the polymerization reaction.

[0101] (Polymerization process) The method for producing a hydrogel according to the present embodiment includes a polymerization step of polymerizing the monomer components in the reaction solution obtained in the reaction solution preparation step. The monomer components are polymerized by the polymerization step to obtain a hydrogel. In the polymerization step, a method for polymerizing the monomer components can be selected depending on the polymerization initiator used, and the reaction solution may be irradiated with light or heated.

[0102] In one aspect of this embodiment, it is preferable to polymerize the monomer components by irradiating the reaction solution containing the photoradical polymerization initiator with light. Specific examples of the light to be irradiated include one or more types of light selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, α-rays, β-rays, and γ-rays, and active electron beams. Among them, ultraviolet light is preferable because it is easy to control the progress of the polymerization reaction and because a photopolymerization device that is widely used can be used. Examples of the light source include a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a xenon lamp, a halogen lamp, a carbon arc lamp, a tungsten lamp, a gallium lamp, an excimer laser, an LED light source, a chemical lamp, a black light lamp, a microwave-excited mercury lamp, and a metal halide lamp. The light irradiation may be performed under an inert gas atmosphere such as nitrogen gas or carbon dioxide gas, or under an atmosphere with a reduced oxygen concentration, or under a normal air atmosphere.

[0103] When the photopolymerization reaction is carried out with ultraviolet light, the ultraviolet irradiation intensity is not particularly limited, but is preferably 10 to 3,000 mW / cm. 2 , more preferably 20 to 1000 mW / cm 2 The ultraviolet irradiation intensity is preferably an intensity in a wavelength region effective for activating a photopolymerization initiator. The time for irradiating light is not limited and can be appropriately set, but is, for example, preferably 1 second to 120 minutes, more preferably 30 seconds to 70 minutes, and further preferably 3 minutes to 60 minutes.

[0104] In one aspect of the present embodiment, it is preferable to polymerize the monomer components by heating the reaction liquid containing the thermal radical polymerization initiator. The temperature and heating time are not limited, but for example, the temperature is raised to 60 to 200° C., and the heating time is preferably about 10 minutes to 30 hours.

[0105] The hydrogel of this embodiment may contain additives either by adding them to the reaction solution or after the gel is formed by the polymerization process. When the additives are added after the gel is formed, the additives can be diffused into the gel by immersing the gel in an aqueous solution (e.g., an aqueous phosphate buffer solution) containing a predetermined concentration of additives (e.g., a dye, a drug, etc.).

[0106] In one embodiment, an additive (such as a drug) encapsulated in a hydrogel can be autonomously released into an external liquid depending on the conditions of the external liquid, and therefore the hydrogel can be used, for example, in a drug delivery system. Examples of additives that can be encapsulated in a hydrogel include, but are not limited to, dyes, proteins, peptides, nucleic acids, other high molecular weight polymers, low molecular weight compounds, etc. The drug may be a therapeutic agent for a disease, a preventive agent, a vaccine, a nutritional supplement, etc.

[0107] The shape of the hydrogel is not particularly limited and may be formed according to the intended use. For example, the gel may be formed into a sheet, film, block, plate, particle, or other shape by known means.

[0108] The hydrogel of the present embodiment is a material that is highly flexible, transparent, highly biocompatible, and exhibits shape memory and self-repair properties, and therefore can be used, for example, as a material having an interface between a living body and an artificial object. The hydrogel of the present embodiment can be suitably used, for example, as a biomaterial, a medical material, a cosmetic, a pharmaceutical product, a quasi-drug, an industrial material, or a hobby material, without being limited thereto. In one embodiment, the hydrogel of the present embodiment can be used as a cell sheet, a cell culture substrate, a cell culture scaffold, or the like. EXAMPLES

[0109] The present invention will be specifically described with reference to the following examples, but the present invention is not limited to these examples.

[0110] <Example 1: Preparation of gel and tensile strength test of the obtained gel> The hydrogel was prepared by the following radical polymerization reaction.

[0111] [ka]

[0112] The method for preparing the gel and the tensile strength test are described. (1) 200 mg of N-acryloyl-nipecotamide (N-acryloyl-piperidine-3-carboxamide) was weighed out and dissolved in 265 μL of deionized water to obtain an aqueous solution. (2) Irgacure 2959 (BASF Japan Ltd., 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone) was dissolved in deionized water to a concentration of 1 mg / mL, and 35 μL of this was added to the aqueous solution obtained in (1) (monomer concentration: 40% by weight). (3) The aqueous solution obtained in (2) was subjected to nitrogen bubbling for 2 minutes. (4) A 1 mm thick poly(dimethylsiloxane) (PDMS) mold cut in the shape of JIS K 6251 No. 7 was placed on a glass slide, and about 420 μL of the nitrogen-bubbled aqueous solution obtained in (3) was added to the mold, and a glass slide was placed on top. This was placed in a transparent bag under a nitrogen atmosphere and irradiated with UV light from a 500 W ultra-high pressure mercury lamp (Ushio Electric Co., Ltd.) for 1 hour (UVC-251S model, SAN-EI ELECTRIC CO., LTD., Osaka, Japan). (5) The UV-irradiated sample obtained in (4) was immersed in water, removed from the mold, and soaked in water overnight to obtain Hydrogel 1. The obtained Hydrogel 1 was transparent. No changes in shape, such as swelling, were observed in the gel after immersion in water. (6) For the hydrogel 1 immersed in water for 1 day in (5), the constricted portion of the gel (width 6 mm, length 10 mm, thickness 1 mm) was pulled at 10 mm / min using a tensile strength tester (68SC-5 model, INSTRON, Norwood, MA) until the hydrogel broke.

[0113] The results of the tensile strength test are shown in Figure 1. Figure 1 is a stress-strain curve, with the horizontal axis representing the extension rate (%) of Hydrogel 1 and the vertical axis representing the tensile stress (kPa). The extension rate (elongation) was calculated for the length of the gel in the tensile direction by (length of gel after extension - length of gel before extension) / length of gel before extension x 100 (%). As shown in Figure 1, the elongation at the time of break of Hydrogel 1 was 1780%, which was very large. The calculated Young's modulus was 8.25 kPa.

[0114] As described above, it was shown that Hydrogel 1 was transparent, hardly swelled when immersed in water, and had high breaking elongation.

[0115] <Example 2: Dynamic viscoelasticity measurement using a rheometer> (1) 480 mg of N-acryloyl-nipecotamide (N-acryloyl-piperidine-3-carboxamide) was weighed out and dissolved in 636 μL of deionized water. (2) Irgacure 2959 was dissolved in deionized water to a concentration of 1 mg / mL, and 84 μL of this was added to the aqueous solution obtained in (1). (3) The aqueous solution obtained in (2) was subjected to nitrogen bubbling for 2 minutes. (4) A 1 mm thick poly(dimethylsiloxane) (PDMS) mold cut into a 3 cm square was placed on a glass slide, and about 1000 μL of the nitrogen-bubbled aqueous solution obtained in (3) was added to the mold, and the glass slide was placed on top. This was placed in a transparent bag under a nitrogen atmosphere and irradiated with UV for 1 hour (UVC-251S model, SAN-EI ELECTRIC CO., LTD., Osaka, Japan). (5) The UV-irradiated sample obtained in (4) was immersed in water and removed from the mold. The sample was then left in water overnight to obtain a hydrogel. (6) The hydrogel obtained in (5) was measured for its viscoelasticity on strain (angular frequency 1 Hz) and frequency (strain 2%) using a rotational rheometer (MCR302 model, Anton Paar, Graz, Austria). The results are shown in Figure 2A and Figure 2B. The storage modulus G' was approximately 3000 Pa, and the loss modulus G" was approximately 1000 Pa.

[0116] <Example 3: Repeated tensile strength test> Hydrogel 1 was obtained by the same method as in (1) to (5) of Example 1.

[0117] (First tensile strength test) The weight of the obtained hydrogel 1 was 395 mg. Using a tensile strength tester (68SC-5 model, INSTRON, Norwood, MA), hydrogel 1 was stretched at 10 mm / min until it was stretched by more than 1000% (left side of Fig. 3A). At this time, the hydrogel released water and its weight decreased to 319 mg. When this stretched hydrogel was immersed in water for 30 minutes without applying stress, the hydrogel returned to its shape before stretching (right side of Fig. 3A) and its weight was 381 mg. (Second tensile strength test) Next, the hydrogel was again pulled at 10 mm / min using a tensile strength tester (68SC-5 model, INSTRON, Norwood, MA) until it was elongated by 1000% or more.

[0118] Figure 3A shows a photograph of the gel after the first tensile strength test and the gel after immersion in water for 30 minutes, which restored the gel's shape. Figure 3B shows the stress-strain curves from the first and second tensile strength tests. The horizontal axis of Figure 3B shows the extension rate, and the vertical axis shows the tensile stress.

[0119] As described above, it was shown that when the hydrogel was stretched and then immersed in water, it returned to its original shape, and the gel's weight and breaking elongation were also restored.

[0120] <Example 4: Recombination by heating> Hydrogel 1 was obtained by the same method as in (1) to (5) of Example 1.

[0121] The obtained hydrogel 1 was cut in half with scissors (left side of Fig. 4A), and these were placed in a 1 mm thick poly(dimethylsiloxane) (PDMS) mold cut in the shape of JIS K 6251 No7, sandwiched between slide glasses, and left to stand together with moistened cotton at 80°C for 1 hour. The sample was then left to stand at room temperature (20-25°C) for 1 hour, and then immersed in water to remove it from the mold.

[0122] The cut sections of the sample that was removed had rejoined (right side of Figure 4A). This demonstrated that the gel has self-repairing capabilities. Figure 4B shows a schematic diagram of the molecular state when the cut gel rejoins when the temperature is raised and lowered. As shown in Figure 4B, when the temperature of the cut gel is raised, hydrogen bonds are broken, promoting molecular motion and causing the molecules at the cut interface of the gel to mix together, and it is presumed that when the temperature is then lowered, hydrogen bonds are also formed at the cut surface of the gel, causing the molecules to rejoin.

[0123] <Example 5: Recombination by freezing and thawing> Hydrogel 1 was obtained by the same method as in (1) to (6) of Example 1.

[0124] The obtained hydrogel 1 was cut in half with scissors, and the two halves were placed in a 1 mm thick poly(dimethylsiloxane) (PDMS) mold cut in the shape of JIS K 6251 No. 7, sandwiched between glass slides, and frozen in a -20°C freezer for 30 minutes. The gel was then left to thaw at room temperature for 30 minutes, and then immersed in water to remove the sample from the mold. The cut portions of the removed sample had recombined, indicating that the gel had self-repairing properties. Figure 5 shows a photograph of the cut gel fragments recombining and being recovered.

[0125] Example 6: Gravimetric analysis of gel The monomer concentration was varied when preparing the gel, and the resulting gel was subjected to gravimetric analysis. (1) 100 mg, 150 mg, 200 mg, and 250 mg of N-acryloyl-nipecotamide (N-acryloyl-piperidine-3-carboxamide) were weighed out and dissolved in 365 μL, 315 μL, 265 μL, and 215 μL of deionized water, respectively, to obtain aqueous solutions. (2) Irgacure 2959 was dissolved in deionized water to a concentration of 1 mg / mL, and 35 μL of this solution was added to each of the aqueous solutions obtained in (1). (3) The aqueous solution obtained in (2) was subjected to nitrogen bubbling for 2 minutes. (4) A 0.5 mm thick poly(dimethylsiloxane) (PDMS) mold cut into a 2 cm square was placed on a glass slide, and about 350 μL of the nitrogen-bubbled aqueous solution obtained in (3) was added to the mold, and the glass slide was placed on top. This was placed in a transparent bag under a nitrogen atmosphere and irradiated with UV for 1 hour (UVC-251S model, SAN-EI ELECTRIC CO., LTD., Osaka, Japan). (5) The UV-irradiated sample obtained in (4) was immersed in water and removed from the mold, and the weight of the obtained hydrogel was measured (weight before immersion in water). (6) The hydrogel of (5) was immersed in water overnight and the weight was measured again (weight after immersion in water). (7) The hydrogel from (6) was freeze-dried (FDU-1200 model, EYELA CO., LTD., Tokyo, Japan) to remove water, and then the weight was measured (weight after freeze-drying). (8) The weight change rate, gel content 1 and gel content 2 were calculated based on the following formula. Weight change rate = (weight after immersion in water) / (weight before immersion in water) x 100[%] Gel content 1 = (weight after freeze-drying) / (weight before immersion in water) x 100[%] Gel content 2 = (weight after freeze-drying) / (weight after immersion in water) x 100[%]

[0126] The results calculated based on the above formula are shown in Figures 6A and 6B. Figure 6A is a graph showing the relationship between the monomer concentration at the time of gel preparation and the weight change rate of the obtained gel due to immersion in water. Gels with a weight change rate of less than 100% shrunk when immersed in water, while gels with a weight change rate of more than 100% swelled when immersed in water. Gels using solutions with monomer concentrations of 20 wt% or 30 wt% shrunk when immersed in water. On the other hand, gels using a solution with a monomer concentration of 50 wt% swelled when immersed in water. The weight of the gel using a solution with a monomer concentration of 40 wt% remained almost unchanged before and after immersion in water, and there was almost no swelling or shrinkage.

[0127] FIG. 6B is a graph showing the relationship between the monomer concentration during gel preparation and gel content 1 (before immersion in water) and gel content 2 (after immersion in water). Gel content 2 was about 30 wt% in all cases, regardless of the monomer concentration during gel preparation. This indicates that when the gel is immersed in water, it swells or shrinks so that the weight concentration of the polymer becomes about 30 wt%, suggesting that a stable phase is formed at a gel content of about 30 wt%.

[0128] Example 7 Number Average Molecular Weight of Polymer in Gel Hydrogels were prepared by varying the concentration of polymerization initiator, and the number average molecular weight of the polymer in the gel was measured. (1) Mixtures containing Irgacure 2959 at concentrations of 4.0, 2.0, 1.0, 0.50, and 0.20 mg / mL in a mixture of 140 μL of water and 210 μL of dimethyl sulfoxide were prepared (Examples 7-1 to 7-5). (2) 150 mg of N-acryloyl-nipecotamide (N-acryloyl-piperidine-3-carboxamide) was added to each of the mixed solutions prepared in (1). (3) The solution obtained in (2) was subjected to nitrogen bubbling for 2 minutes. (4) A 0.5 mm thick poly(dimethylsiloxane) (PDMS) mold cut into a 2 cm square shape was placed on a glass slide, and about 350 μL of the aqueous solution bubbled with nitrogen in (3) was added to the mold, and the glass slide was placed on top. This was placed in a transparent bag under a nitrogen atmosphere and irradiated with 500 W UV for 1 hour (UVC-251S model, SAN-EI ELECTRIC CO., LTD., Osaka, Japan). (5) The UV-irradiated sample obtained in (4) was immersed in water and removed from the mold. The sample (hydrogel) was then immersed in water overnight and its weight was measured (weight after immersion in water). (6) After (5), the hydrogel was freeze-dried (FDU-1200 model, EYELA CO., LTD., Tokyo, Japan) and its weight was measured (weight after freeze-drying). (7) The gel content was calculated based on the following formula. Gel content = (weight after freeze-drying) / (weight after immersion in water) x 100[%] (8) The amount of monomer that actually became a hydrogel was calculated from the weight after freeze-drying, and the average degree of polymerization was calculated by dividing the number of moles by the number of moles of the initiation point predicted from the reaction initiator (the initiator produces two radicals per molecule). The number-average molecular weight of the polymer was calculated by multiplying this average degree of polymerization by the molecular weight of the repeating unit in the polymer (182.1 g / mol).

[0129] The above measurement and calculation results are shown in Table 1 below.

[0130] [Table 1]

[0131] As described above, it was shown that gels having different number average molecular weights of polymers can be formed by changing the concentration of the polymerization initiator.

[0132] Example 8: Gel containing additives <Example 8-1: Hydrogel containing gelatin> (1) 200 mg of N-acryloyl-nipecotamide (N-acryloyl-piperidine-3-carboxamide) was measured out. (2) The monomer from (1) was dissolved in 265 μL of aqueous solution containing 1.0 wt % or 0.25 wt % gelatin. (3) Irgacure 2959 was dissolved in deionized water to a concentration of 1 mg / mL, and 35 μL of this was added to the aqueous solution containing the monomer and gelatin obtained in (2). (4) The aqueous solution obtained in (3) was subjected to nitrogen bubbling for 2 minutes. (5) A 1 mm thick poly(dimethylsiloxane) (PDMS) mold cut in the shape of JIS K 6251 No. 7 was placed on a glass slide, and about 420 μL of the nitrogen-bubbled aqueous solution obtained in (4) was added to the mold, and a glass slide was placed on top. This was placed in a transparent bag under a nitrogen atmosphere and irradiated with UV for 1 hour (UVC-251S model, SAN-EI ELECTRIC CO., LTD., Osaka, Japan). (6) The UV-irradiated sample obtained in (5) was immersed in water to remove it from the mold, and the sample was left in water overnight. A photograph of the resulting gel (gelatin concentration 0.25 wt%) is shown in Figure 8A. (7) The hydrogel soaked in water for 1 day in (6) was pulled at 10 mm / min using a tensile strength tester (68SC-5 model, INSTRON, Norwood, MA) until the hydrogel broke.

[0133] The results are shown in Figure 8B. By including gelatin, the gel's breaking elongation was greater than that of the gel that did not contain gelatin (Figure 1). The gel containing 0.25 wt% gelatin achieved an extension rate of about 4000%. This is presumably because the inclusion of gelatin results in the formation of an interpenetrating polymer network (IPN structure), which increases the intermolecular forces and molecular crowding compared to gels that do not contain gelatin, thereby affecting the mechanical properties of the gel.

[0134] <Example 8-2: Gel containing alginic acid> (1) 200 mg of N-acryloyl-nipecotamide (N-acryloyl-piperidine-3-carboxamide) was measured out. (2) The monomer from (1) was dissolved in 265 μL of an aqueous solution containing 2.0 wt % sodium alginate. (3) Irgacure 2959 was dissolved in deionized water to a concentration of 1 mg / mL, and 35 μL of this was added to the aqueous solution containing sodium alginate and monomer obtained in (2). (4) The aqueous solution obtained in (3) was subjected to nitrogen bubbling for 2 minutes. (5) A 1 mm thick poly(dimethylsiloxane) (PDMS) mold cut in the shape of JIS K 6251 No. 7 was placed on a glass slide, and about 420 μL of the nitrogen-bubbled aqueous solution obtained in (4) was added to the mold, and the glass slide was placed on top. This was placed in a transparent bag under a nitrogen atmosphere and irradiated with UV for 1 hour (UVC-251S model, SAN-EI ELECTRIC CO., LTD., Osaka, Japan). (6) The UV-irradiated sample obtained in (5) was immersed in water and removed from the mold. The sample was then left in water overnight to obtain a hydrogel. (7) A sample was prepared separately from (6) by the same method as (1)–(5), and was immersed overnight in a 0.1 M aqueous solution of CaCl2 instead of water. (8) Using a tensile strength testing machine (68SC-5 model, INSTRON, Norwood, MA), the gel immersed in water in (6) and the gel immersed in the aqueous CaCl2 solution in (7) were pulled at 10 mm / min until the hydrogel broke (Figure 8D). (9) In addition, a gel was prepared separately from (8) by immersing it in an aqueous solution of 0.1 M CaCl2 in the same manner as in (7), and the gel was cut in the middle. (10) The gel cut in (9) was placed in a JIS K 6251 No. 7 mold, 50 μL of 1 M CaCl2 solution was dropped onto the cut part, and the gel was sandwiched between glass slides and left to stand for 2 hours. (11) The sample obtained in (10) was immersed in water, the slide glass was removed, and the sample was recovered. It was confirmed that the gel had reassembled (Figure 8E). This is because the alginic acid in the gel had reassembled with Ca. 2+ It is presumed that the repair properties are achieved by forming a cross-linked structure.

[0135] FIG. 8C shows the gel (6) immersed in water not containing CaCl (-Ca 2+ ), and the gel in (7) immersed in an aqueous solution of CaCl2 (+Ca 2+ ) is shown. The gel (-Ca) immersed in water only 2+ ) was observed to swell, whereas the gel immersed in an aqueous solution of CaCl2 (+Ca 2+ ) did not swell and was a hard gel. It is presumed that the gel immersed in water alone swelled due to the hydrophilic nature of the alginic acid in the gel. On the other hand, it is presumed that the gel immersed in the CaCl2 aqueous solution did not swell easily because the alginic acid in the gel was cross-linked by calcium.

[0136] Figure 8D shows the results of the tensile strength test in (8). The gel immersed in an aqueous solution of CaCl2 had a larger breaking elongation than the gel immersed in water not containing CaCl2.

[0137] Figure 8E is a photograph of the gels in (10) and (11). The cut gels were repaired and reassembled.

[0138] As mentioned above, Ca 2+ It was shown that the gel left overnight in the presence of ions was harder and had a larger breaking elongation than the gel immersed in water alone. It was also confirmed that the gel containing alginic acid also has self-repairing properties. Alginic acid is a compound that contains Ca 2+ A cross-linking structure is created through ions. This creates a polymer network formed by hydrogen bonds in poly(N-acryloyl-nipecotamide), as well as alginate and Ca 2+ It is presumed that an IPN structure was formed due to the cross-linking structure consisting of ions, which changed the physical properties of the gel.

[0139] Example 9: Addition of dye (Rose Bengal) to gel (1) Hydrogel 1 was prepared by the same method as in (1) to (5) of Example 1. 208 mg of this hydrogel piece was immersed in 50 mL of a 1 mg / mL aqueous solution of rose bengal (RB) for 1 hour. (2) The weight of the hydrogel after (1) was measured and found to be 386 mg. The gel was stained red, indicating that RB had been incorporated into the gel. (3) The hydrogel was immersed in 50 mL of deionized water, and the UV-Vis spectrum of the external solution was measured (wavelengths 400-800 nm) after 1, 3, 5, 10, 20, 30, 45, and 60 minutes. The maximum absorption wavelength of RB is 549 nm. (4) To calculate the amount of RB released, a calibration curve was prepared from the UV-Vis spectrum using RB aqueous solutions with concentrations of 0.0025, 0.005, and 0.01 mg / mL. Based on this calibration curve, the amount of RB released was estimated from the absorbance of the external solution at a wavelength of 549 nm.

[0140] Figure 9A shows the results of measuring the absorbance at 549 nm, which is the maximum absorption wavelength of RB, for the external solution when a gel containing RB was immersed in water. Figure 9B shows the results of calculating the amount of RB released based on the calibration curve from the results of Figure 9A. These results show that immersing a gel containing RB in water gradually releases RB into the water (external solution). In (2), the hydrogel containing RB weighed 386 mg, but the gel after immersion in water for 60 minutes weighed 195 mg.

[0141] Example 10: Light transmittance of gel (1) 360 mg of N-acryloyl-nipecotamide was weighed into a 1.5 mL disposable plastic cuvette (Fisher Scientific, light path length 1 cm) and dissolved in 540 μL of an aqueous solution containing Irgacure 2959 at a concentration of 0.1 mg / mL. (2) The aqueous solution obtained in (1) was subjected to nitrogen bubbling for 2 minutes and then covered with parafilm. (3) The sample obtained in (2) was irradiated with 500 W UV for 1 hour (UVC-251S model, SAN-EI ELECTRIC CO., LTD., Osaka, Japan). (4) The light transmittance in the visible region was measured using a UV-Vis spectrophotometer (V730, manufactured by JASCO Corporation). (The gel thickness, i.e., the optical path length, was 1 cm.)

[0142] The results of the light transmittance measurements are shown in Figure 10. The light transmittance in the visible region was approximately 80% or more, indicating that the gel was transparent. (The light transmittance at wavelengths of 700 nm, 600 nm, and 500 nm was 89.4%, 89.5%, and 87.7%, respectively.)

[0143] <Example 11: Synthesis of N-acryloyl-2-aminobutyramide, preparation of gel using same, and tensile strength test of gel> (Synthesis of N-acryloyl-2-aminobutyramide) (1) 2 g (0.0144 mmol) of 2-aminobutanamide hydrochloride was dissolved in 25 mL of 1.5 M aqueous potassium carbonate solution. (2) 1.54 mL (0.0187 mmol) of acrylic acid chloride was dissolved in 10 mL of diethyl ether. (3) The solution obtained in (2) was stirred while being cooled in an ice bath, and the aqueous solution obtained in (1) was slowly added dropwise thereto. (4)(3) was stirred in the ice bath for 20 hours without adding additional ice. (5) The sample obtained in (4) was cooled again in an ice bath for 30 minutes. (6) The sample obtained in (5) was subjected to vacuum filtration to recover the precipitate, which was then washed with ice-cold water. (7) The precipitate washed in (6) was dried in vacuum, and then the sample was recovered. Yield: 1.39 g, yield: 61.7%. The obtained N-acryloyl-2-aminobutyramide 1 The 1 H NMR chart is shown in Figure 16.

[0144] <Example 11-1: Preparation of gel using N-acryloyl-2-aminobutyramide> (1) 200 mg of N-acryloyl-2-aminobutyramide was dissolved in 1.8 mL of deionized water to prepare a monomer solution (monomer concentration: 10 wt%). (2) Irgacure 2959 was dissolved in deionized water to a concentration of 1.0 mg / mL to prepare an Irgacure solution. (3) The monomer solution (1), the Irgacure solution (2), and deionized water were mixed in the amounts shown in Table 2 to prepare sample solutions (gelling solutions) with monomer concentrations of 1 wt%, 5 wt%, and 9 wt%. (4) Nitrogen was bubbled through each sample solution for 2 minutes. (5) The bottle containing the sample solution was irradiated with UV light for 1 hour (UVC-251S model, SAN-EI ELECTRIC CO., LTD., Osaka, Japan). (6) The presence or absence of gelation was evaluated by a bottle tightening test in which the bottle was turned upside down.

[0145] [Table 2]

[0146] Figure 11A shows a photograph of the results of the bottle tightening test. When the bottle was turned upside down, samples with monomer concentrations of 1wt% and 5wt% were fluid and the samples fell, but those with 9wt% were not fluid and did not fall. This indicates that when the monomer concentration is 9wt% or higher, a solid-like material with sufficient hydrogen bonds formed, i.e., a gel, can be obtained.

[0147] <Example 11-2: Gelation of N-acryloylnipecotamide / N-acryloyl-2-aminobutyramide> (1) 200 mg of N-acryloyl-2-aminobutyramide was dissolved in 1.8 mL of deionized water (monomer concentration: 10 wt%). (2) Irgacure 2959 was dissolved in deionized water to a concentration of 1.0 mg / mL. (3) 200 mg of N-acryloylnipecotamide was weighed out, and 100 μL of the N-acryloyl-2-aminobutyramide solution obtained in (1), 170 μL of deionized water, and 30 μL of the Irgacure 2959 solution obtained in (2) were added to obtain a sample solution. (4) The sample solution obtained in (3) was subjected to nitrogen bubbling for 2 minutes. (5) A 1 mm thick poly(dimethylsiloxane) (PDMS) mold cut into the shape of JIS K6251 No. 7 was placed on a glass slide, and about 420 μL of the nitrogen-bubbled aqueous solution obtained in (4) was added to the mold, and a glass slide was placed on top. This was placed in a transparent bag under a nitrogen atmosphere and irradiated with 500 W UV for 1 hour (UVC-251S model, SAN-EI ELECTRIC CO., LTD., Osaka, Japan). (6) The UV-irradiated sample obtained in (5) was immersed in water and removed from the mold, and the sample was then immersed in water overnight. (7) The gel soaked in water overnight in (6) was subjected to a tensile strength test in the same manner as in Example 1.

[0148] FIG. 11B is a photograph of the gel (left) immediately after removal from the mold in (6) above, and a transparent gel (right) obtained by soaking in water overnight. FIG. 11C is a graph showing the results of the tensile strength test performed in (7) above. The elongation at break of the hydrogel was 810%. The calculated Young's modulus was 15.08 kPa. It was shown that the copolymer of N-acryloylnipecotamide and N-acryloyl-2-aminobutyramide was harder than the homopolymer of N-acryloyl-nipecotamide in Example 1.

[0149] <Synthesis Example> The following novel compounds were synthesized as monomers that can be used to produce the hydrogel of this embodiment.

[0150] <Synthesis Example 1: Synthesis of N-acryloyl-2-piperidinecarboxamide> N-acryloyl-2-piperidinecarboxamide represented by the following formula (15) was synthesized by the following method.

[0151] [ka] 2-Piperidinecarboxamide (3.91 g) was added to dimethylformamide (80 mL), stirred at 45° C. for 30 minutes to dissolve, and then allowed to stand at room temperature. Then, triethylamine (4.88 mL) was added under an argon gas atmosphere at 4° C. A solution of acrylic acid chloride (3.27 mL) dissolved in dimethylformamide (20 mL) was slowly added dropwise to this reaction solution, and after the dropwise addition, the mixture was stirred at room temperature overnight. After stirring, triethylamine hydrochloride was removed by filtration, the solution was concentrated with an evaporator, and the solution containing N-acryloyl-2-piperidinecarboxamide was separated by silica gel chromatography (Wakogel C200, Fujifilm Wako Pure Chemical Industries, Ltd.) (elution solution: acetone:hexane = 7:3 (volume ratio)), concentrated again with an evaporator (about 30 mL), and an appropriate amount of ethyl acetate (about 50 mL) was added to the concentrated solution to precipitate a white component, which was collected by filtration and drying to obtain N-acryloyl-2-piperidinecarboxamide (1.73 g). When developed with thin-layer silica gel chromatography (developing solution: acetone:hexane = 7:3 (volume ratio)), a UV absorption spot was obtained (Rf value = 0.33 to 0.43). N-acryloyl-2-piperidinecarboxamide 1 H- 13 The C HSQC NMR chart is shown in FIG.

[0152] <Synthesis Example 2: Synthesis of N-acryloyl-4-piperidinecarbonitrile> N-acryloyl-4-piperidinecarbonitrile represented by the following formula (33) was synthesized by the following method. This compound can be used as monomer (B) copolymerizable with monomer (A).

[0153] [ka] 4-Piperidinecarbonitrile (5.06 mL) (Sigma-Aldrich) was added to a mixed solution of acetone (80 mL) and triethylamine (6.7 mL), and the mixture was stirred at 4°C under an argon gas atmosphere. A solution of acrylic acid chloride (4.3 mL) dissolved in acetone (20 mL) was added dropwise to the reaction solution, and the mixture was stirred overnight. After stirring, triethylamine hydrochloride was removed by filtration, and the solution was concentrated with an evaporator. The solution containing N-acryloyl-4-piperidinecarbonitrile was separated by silica gel chromatography (elution solution: ethyl acetate:acetone = 5:1 (volume ratio)), and the solution was concentrated again with an evaporator to obtain liquid N-acryloyl-4-piperidinecarbonitrile (0.27 g). When developed with thin-layer silica gel chromatography (developing solution: ethyl acetate:acetone = 5:1 (volume ratio)), a spot of UV absorption was obtained (Rf value = 0.48-0.58). N-Acryloyl-4-piperidinecarbonitrile 1 H- 13 The C HSQC NMR chart is shown in FIG.

[0154] <Synthesis Example 3: Synthesis of N-acryloyl-3,5-piperidinedicarboxamide> N-acryloyl-3,5-piperidinedicarboxamide represented by the following formula (11) was synthesized by the following method.

[0155] [ka] Oxalyl chloride (506 mL) was added dropwise to 3,5-pyridinedicarboxylic acid (100 g) under an argon gas atmosphere and refluxed (16 hours). After refluxing, the precipitated components were collected using an evaporator, dissolved in acetonitrile (1.8 L), and ammonia gas was injected into the solution. The precipitate was collected by filtration, suspended in an appropriate amount of saturated sodium bicarbonate solution, treated (70°C, 5 minutes), and allowed to stand at room temperature to obtain a precipitate. The precipitate was washed with water, acetonitrile, and diethyl ether in that order, and the target compound intermediate 1 (pyridine-3,5-dicarboxamide) was obtained using a rotary evaporator.

[0156] Pyridine-3,5-dicarboxamide (112 g) was added dropwise to a 4 molar concentration of hydrochloric acid-1,4-dioxane solvent under an argon atmosphere and stirred at room temperature for 16 hours. The solvent was then dried and solidified on a rotary evaporator under an inert atmosphere, and the solid was crushed with diethyl ether. This was dried under vacuum to obtain intermediate 2 (pyridine-3,5-dicarboxamide hydrochloride).

[0157] A platinum oxide methanol solution (platinum oxide (9.4 g)) was added to a methanol aqueous solution (methanol:water = 9:1 (volume ratio)) (3 L) in which pyridine-3,5-dicarboxamide hydrochloride (104.5 g) was dissolved, and the mixture was stirred in a sealed environment under hydrogen gas (150 psi) (80 °C, 24 hours). The reaction mixture was then filtered through Celite, the filtrate was evaporated in a rotavapor, and the residue was co-distilled with toluene three times and dried under vacuum to obtain intermediate 3 (piperidine-3,5-dicarboxamide hydrochloride).

[0158] Piperidine-3,5-dicarboxamide hydrochloride (48.6 g) was dissolved in dimethylformamide (1.2 L), potassium carbonate (63.9 g) was added, and the mixture was stirred at room temperature (30 min). The reaction solution was then cooled to 0° C., acryloyl chloride (23.3 g) was added, and the mixture was stirred at room temperature (16 h). The hydrochloride was filtered and removed, and the residue was concentrated with Rotavapol, and purified by column chromatography using Florisil as the stationary phase and 20% methanol-dichloromethane solution as the eluent to obtain the target compound (N-acryloylpiperidine-3,5-dicarboxamide). The NMR chart of N-acryloylpiperidine-3,5-dicarboxamide is shown in FIG. 14.

[0159] <Synthesis Example 4: Synthesis of acryloyl-N-(2-amino-2-oxoethyl)piperidine-3-carboxamide> Acryloyl-N-(2-amino-2-oxoethyl)piperidine-3-carboxamide represented by the following formula (12) was synthesized by the following method. The reaction formula is as follows.

[0160] [ka] A mixed solution of 1-Boc-nipecotic acid (1) (163 g), triethylamine (116 mL), and THF (1.97 L) was added dropwise to a solution of isobutyl chloroformate (111 mL) in tetrahydrofuran (1.32 L) under ice cooling. After stirring for 1 hour, the reaction solution was filtered. The filtrate obtained was added dropwise to a mixed solution of glycinamide hydrochloride (196 g), sodium hydroxide (70.6 g), tetrahydrofuran (1.02 L), and water (510 mL) under ice cooling. After stirring overnight at room temperature, an aqueous NaCl solution was added to the reaction solution, and the mixture was extracted with ethyl acetate. The organic layer obtained was washed with an aqueous 1M sodium hydroxide solution, dried over magnesium sulfate, filtered, and the filtrate obtained was concentrated. Intermediate 2 (209 g) was obtained by the above operations.

[0161] To a solution of intermediate 2 in dichloromethane (1.39 L), trifluoroacetic acid (663 mL) was added dropwise. After stirring for 1 hour, the reaction solution was concentrated to obtain viscous intermediate 3 (229 g).

[0162] Sodium carbonate (243 g) was added to a solution of intermediate 3 (229 g) in methanol (1.76 L), cooled to -20°C or lower, and acryloyl chloride (185 mL) was added dropwise. After stirring for 3 hours, the reaction solution was filtered. The filtrate was concentrated, and an acetonitrile-methanol solvent (acetonitrile:methanol = 2:1 (volume ratio) (1.0 L) was added to the residue, and the mixture was filtered. The filtrate was concentrated, and the resulting crude product was purified by silica gel column chromatography to obtain the desired acryloyl-N-(2-amino-2-oxoethyl)piperidine-3-carboxamide (66.8 g). 1 H- 13 The C HSQC NMR chart is shown in FIG.

[0163] Although preferred embodiments of the present invention are shown herein, it will be apparent to those skilled in the art that such embodiments are provided for illustrative purposes only, and that various modifications, changes, and substitutions may be made by those skilled in the art without departing from the present invention. It should be understood that various alternative embodiments of the invention described herein may be used in practicing the present invention. In addition, the contents of all publications, including patents and patent applications, referenced in this specification should be construed as being incorporated by reference as if set forth herein.

Claims

1. A hydrogel comprising a polymer (A) having a structural unit derived from one or more monomers (A) selected from the group consisting of a compound represented by the following formula (1) and a compound represented by the following formula (2): 【Chemistry 1】 (In formula (1), R 11 is hydrogen or a methyl group, R 12 ~R 16 are each independently hydrogen, -C(=O)NH 2 or -C(=O)-NH-CH 2 -C(=O)-NH 2 and R 12 ~R 16 At least one of the following is -C(=O)NH 2 Or -C(=O)-NH-CH 2 -C(=O)-NH 2 It is.) 【Chemistry 2】 (In formula (2), R 21 is hydrogen or a methyl group, R 22 is -C 2 H 5 Or -C 3 H 7 It is.)

2. The hydrogel of claim 1 , wherein the polymer (A) is a homopolymer.

3. The hydrogel according to claim 1 or 2, wherein the polymer (A) is a copolymer.

4. The hydrogel according to claim 3 , wherein the polymer (A) is a copolymer further comprising a constituent unit derived from a monomer (B) that is copolymerizable with the monomer (A).

5. The hydrogel according to claim 1 or 2, wherein the monomer (A) comprises a compound represented by the formula (1).

6. The hydrogel according to claim 1 or 2, wherein the monomer (A) comprises one or more compounds selected from the group consisting of compounds represented by the following formulas (11) to (15): 【Chemistry 3】

7. The hydrogel according to claim 1 or 2, wherein the monomer (A) comprises N-(meth)acryloyl nipecotamide and / or N-(meth)acryloyl-2-aminobutyramide.

8. The hydrogel according to claim 3 , wherein the polymer (A) has a structure represented by the following formula (31) and / or the following formula (32): 【Chemistry 4】 (In formula (31), m and n each independently represent an integer of 1 or more.) 【Chemistry 5】 (In formula (32), m and n each independently represent an integer of 1 or more.)

9. The hydrogel of claim 1 or 2, wherein the monomer (A) comprises N-acryloylnipecotamide.

10. The hydrogel of claim 1 or 2, which is transparent.

11. The hydrogel according to claim 1 or 2, further comprising an additive that does not constitute the polymer (A).

12. The hydrogel of claim 11 , wherein the additive is alginic acid and / or gelatin.

13. The hydrogel according to claim 1 or 2, wherein the weight percentage of the polymer (A) in the hydrogel is 5 to 60% by weight.

14. The hydrogel according to claim 1 or 2, wherein the weight percentage of the polymer (A) in the hydrogel is 20 to 50% by weight.

15. 3. The hydrogel according to claim 1, wherein the weight percentage of the polymer (A) when immersed in water for 24 hours is 20 to 40% by weight.

16. The hydrogel according to claim 1 or 2, wherein the number average molecular weight of the polymer (A) is 6,500 to 1,000,000 Da.

17. The hydrogel according to claim 1 or 2, wherein the number average molecular weight of the polymer (A) is 31,000 Da or more.

18. The hydrogel according to claim 1 or 2, having an elongation at break of 1500% or more in a tensile test in accordance with JIS K6251:2017, dumbbell-shaped No.

7.

19. A step of preparing a reaction liquid containing an aqueous solvent, a polymerization initiator, and a monomer component containing one or more monomers (A) selected from the group consisting of a compound represented by the following formula (1) and a compound represented by the following formula (2); A step of polymerizing a monomer component in the reaction liquid; A method for producing a hydrogel comprising the steps of: 【Chemistry 6】 (In formula (1), R 11 is hydrogen or a methyl group, R 12 ~R 16 are each independently hydrogen, -C(=O)NH 2 or -C(=O)-NH-CH 2 -C(=O)-NH 2 and R 12 ~R 16 At least one of the following is -C(=O)NH 2 Or -C(=O)-NH-CH 2 -C(=O)-NH 2 It is.) 【Chemistry 7】 (In formula (2), R 21 is hydrogen or a methyl group, R 22 is -C 2 H 5 Or -C 3 H 7 It is.)

20. The method for producing a hydrogel according to claim 19, wherein the concentration of the monomer (A) in the reaction solution is 20 to 60% by weight.

21. The method for producing a hydrogel according to claim 19 or 20, wherein the polymerization initiator is a photoradical polymerization initiator.